Oscillating Electric Machines and their Place in the Whole of Electric Machines - Kudarauskas, S. (Elektronika ir Elektrotechnika, 2000)
This article presents the classification of all electrical machines by specific temporal (continuous, periodical, impulse) and spatial (rotary, linear, complex) features of mechanical movement. From theoretical point of view is purposive to group the electrical machines by the temporal features of mechanical movement. It is proved that the structure of the magnetic circuit of oscillating machines may be different from the structure of the ordinary machines. The main operating regime of the oscillating synchronous motors is a steady periodic one, which can be performed by the symbolic method (in analogy to the analysis of AC circuits). The fields of the oscillating machines use are discussed.